Patients’ Expectations of Foot and Ankle Surgery - Scott Ellis MD; Elizabeth Cody MD; Jayme Koltsov PhD; Anca Marinescu BA; Carol Mancuso MD (Foot & Ankle Orthopaedics, 2017)
Category: Patient expectations Introduction/Purpose: Patients’ expectations from orthopaedic surgery may strongly affect postoperative satisfaction and have been shown to relate to many different factors, including age, sex, functional status, and health. However, the diverse diagnoses in foot and ankle surgery may also influence expectations. While pain relief tends to be the predominant expectation of orthopaedic foot and ankle patients, there are certain expectations that may be more important for patients with certain diagnoses. In this study, we aimed to analyze differences in patients’ expectations among the major surgical diagnoses seen in foot and ankle practices. Methods: 352 patients undergoing elective foot and ankle surgery by six orthopaedic foot and ankle surgeons were enrolled over eight months. Patients completed the Foot & Ankle Surgery Expectations Survey preoperatively, as well as the Foot & Ankle Outcome Score (FAOS), Short Form (SF)-12, Patient Health Questionnaire (PHQ)-8, Generalized Anxiety Disorder 7-item scale (GAD-7), and pain visual analog scale (VAS). The expectations survey is scored from 0-100 with higher scores indicating greater expectations. Each of its 23 items can also be assessed independently. Differences in expectations scores between diagnoses were analyzed with t-tests and analysis of variance (ANOVA). Differences in the number of expectations and number of expectations with complete improvement expected were analyzed with Mann-Whitney U and Kruskal Wallis tests. Results: Patients with a diagnosis of ankle instability or osteochondral lesion (OCL) had higher expectations scores (p = 0.004) and more often expected complete improvement (p = 0.024) compared to patients with other diagnoses (Table). Patients with hallux valgus had lower expectations scores (p = 0.005) than patients with other diagnoses. Patients with mid- or hindfoot arthritis also had lower expectations scores (p = 0.006) and even more significantly, had an average of only 2.4 expectations with complete improvement expected, while all other patients averaged 8.4 (p < 0.001). Expectations that were relatively unique to specific diagnoses included increased shoe variety for hallux valgus and hallux rigidus, improved appearance for hallux valgus, and improved ability to run for exercise for ankle instability or OCL. Conclusion: Patients’ expectations of foot and ankle surgery vary widely by diagnosis. Higher expectations among patients with ankle instability/OCL may be related to worse functional and mental health status (Table). Lower expectations among patients with hallux valgus and mid- or hindfoot arthritis may be attributable in part to patients’ recognition of the difficulty of treating their condition. Preoperative counseling by their surgeons regarding realistic expectations may also be a factor. We can use the findings of this study to predict what expectations are most important to patients with different diagnoses and to guide how we counsel them prior to surgery.